Third CECOG consensus on the systemic treatment of non-small-cell lung cancer - Brodowicz, Thomas; Manegold, Christian (Annals of oncology, 2012)
Abstract. The current third consensus on the systemic treatment of non-small-cell lung cancer (NSCLC) builds upon and updates similar publications on the subje